Bioinsecticides based on neem (Azadirachta indica) and rue (Ruta graveolens) against Agrotis ipsilon - Souza, Maria Roberta Rodrigues de; Lima, Roberta Camile da Silva; Dantas, Liliane Gallindo; Frensch, Gustavo (Comunicata Scientiae, 2024)
Agrotis ipsilon is an important pest of several crops, where it causes damage to various parts of the plant such as stems, roots, leaves and tubers. Due to the growing demand for controlling these pests, there is a constant need for new products as the organisms acquire resistance after continuous contact. And this also generates a demand for bioinsecticides, which normally pose a lower health risk and are less harmful to the environment. Among the plants commonly used as insecticides are neem and rue, which have already been studied for several pests, although never together. This work aimed to determine the insecticidal activity of a natural insecticide derived from a mixture of neem and rue, commonly used in the region of Senhor do Bonfim-BA against A. ipsilon. Four different solutions were prepared, containing a) 20 neem leaves, 10 rue leaves and 5 A. ipsilon caterpillars, b) 20 neem leaves and 10 rue leaves, c) 20 neem leaves and d) 10 rue leaves. Water was tested as control. In the tests carried out, both the mixture popularly used in the region, containing neem, rue, and A. ipsilon caterpillars, as well as the solution containing only neem and rue had good results, killing all caterpillars in 72 hours. Isolated plant extracts did not obtain good results, only delaying the formation of pupae for neem extracts. Therefore, the mixture of Neem and Rue showed good insecticidal potential against A. ipsilon, with much higher activity than its isolated components.